Human Immunodeficiency Virus Infection Is Associated With Preterm Delivery Independent of Vaginal Microbiota in Pregnant African Women. (13th November 2019) - Gudza-Mugabe, Muchaneta; Havyarimana, Enock; Jaumdally, Shameem; Garson, Kirsty Lee; Lennard, Katie; Tarupiwa, Andrew; Mugabe, Fortunate; Marere, Tarisai; Mavenyengwa, Rooyen T; Masson, Lindi; Jaspan, Heather B
Abstract: Background: During pregnancy, the vaginal microbiota is relatively stable. However, African women have more diverse vaginal microbiota than their European counterparts, in addition to high human immunodeficiency virus (HIV) prevalence and risk of adverse birth outcomes. Although HIV is associated with alterations in vaginal microbiota and inflammation in nonpregnant women, these relationships are underexplored in pregnant women. Methods: In this study, we characterize the vaginal microbiota and immune factors in pregnant African women who were HIV-uninfected (n = 314) versus HIV-infected (n = 42). Mucosal samples were collected once at the enrollment visit (between 15 and 35 weeks of gestation) and women were followed until delivery. Results: Vaginal microbial communities of pregnant women with HIV were significantly more diverse than women without HIV ( P = .004), with community structure also differing by HIV status ( P = .002, R 2 = 0.02). Human immunodeficiency virus infection was also associated with increased risk of preterm birth (PTB) (31% versus 15.3%; P = .066). In a multivariate analysis, HIV infection was independently associated with diverse vaginal community state type (CST)-IVA ( P = .005) and CST-IVB ( P = .018) as well as PTB ( P = .049). No association between HIV status and cytokine concentrations was found. Conclusions: Longitudinal studies with accurate gestational age assessment would be important to confirm these relationships. Abstract : Pregnant women with HIV have more diverse vaginal communities and altered community structure compared with pregnant uninfected women. However, preterm birth was associated with HIV infections independent of vaginal community state type.